Implementation of the Second Generation Crime Prevention Through Environmental Design (CPTED) Theory to Strengthen the Assimilation of Correctional Inmates with the Community in Region "X" through Social Projects - Imam Suyudi; Adrianus Eliasta Meliala (Dinasti International Journal of Education Management And Social Science, 2024)
This study examines the implementation of the Second Generation Crime Prevention Through Environmental Design (CPTED) theory to enhance the assimilation of Correctional Inmates (WBP) with the community in Region "X" through a social project. The purpose of this research is to address the challenges of reintegration faced by WBP, such as negative stigma and lack of community support. The research method employed is qualitative, utilizing field observations and unstructured interviews. The results indicate that the Gen 2 CPTED-based social project successfully strengthened the social relationship between Correctional Inmates (WBP) and the community, while reducing the risk of recidivism. In conclusion, the implementation of CPTED Gen 2 is effective in supporting the assimilation of WBP, encouraging active community participation, and is important to be used more widely.